SWI/SNF complex-deficient soft tissue neoplasms: An update - Schaefer, Inga-Marie; Hornick, Jason L. (Seminars in diagnostic pathology, 2021)
•Mutations of the SWI/SNF chromatin remodeling complex are found in >20% of cancers.•SMARCB1 is most frequently inactivated in SWI/SNF-deficient soft tissue neoplasms.•SMARCA4-deficient thoracic sarcomas are characterized by SMARCA4 and SMARCA2 loss.•Most SWI-SNF-deficient soft tissue neoplasms share rhabdoid cytomorphology. The SWItch Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex is a large multi-subunit protein assembly that orchestrates chromatin compaction and accessibility for gene transcription in an ATP-dependent manner. As a key epigenetic regulator, the SWI/SNF complex coordinates gene expression, cell proliferation and differentiation, and its biologic functions, in part, antagonize the polycomb repressive complex 2. The mammalian SWI/SNF complex consists of 15 subunits encoded by 29 genes, some of which are recurrently mutated in human cancers, in the germline or sporadic setting. Most SWI/SNF-deficient tumors share common “rhabdoid” cytomorphology. SMARCB1 (INI1) is the subunit most frequently inactivated in soft tissue neoplasms. Specifically, SMARCB1 deficiency is observed as the genetic hallmark in virtually all malignant rhabdoid tumors, and most cases of epithelioid sarcoma and poorly differentiated chordoma. In addition, subsets of myoepithelial carcinoma (10–40%), extraskeletal myxoid chondrosarcoma (20%), epithelioid schwannoma (40%), and epithelioid malignant peripheral nerve sheath tumor (70%) demonstrate SMARCB1 loss. The gene encoding the SS18 subunit is involved in the SS18-SSX rearrangement, which is pathognomonic of synovial sarcoma and indirectly inactivates SMARCB1. Finally, undifferentiated SMARCA4-deficient thoracic sarcomas are defined by SMARCA4 subunit inactivation, leading to SMARCA4 and SMARCA2 loss. Rarely, inactivation of alternate but biologically equivalent key regulators can substitute for canonical subunit deficiency, such as SMARCA4 inactivation in cases of SMARCB1-retained epithelioid sarcoma. This review briefly highlights SWI/SNF complex biologic functions and its roles in human cancer and provides a detailed update on recent advances in soft tissue neoplasms with canonical SWI/SNF complex deficiency, correlating morphologic, genomic, and immunohistochemical findings.